Binary polynomial transforms and nonlinear digital filters - Agaian, S. S (Monographs and textbooks in pure and applied mathematics, 1995)
This unique reference offers a unified presentation of the theory of binary polynomial transforms and details their numerous applications in nonlinear signal processing. Binary Polynomial Transforms and Nonlinear Digital Filters introduces the Rademacher logical functions...considers fast algorithms for computing Rademacher and polynomial logical functions...focuses attention on general auto- and cross-correlation functions...analyzes Boolean functions via binary polynomial transforms...studies standard median and order statistic filters...explores the statistical properties of stack filters...and much more.